2018
DOI: 10.1158/1055-9965.epi-17-0523
|View full text |Cite
|
Sign up to set email alerts
|

Potential Medication-Related Problems in Older Breast, Colon, and Lung Cancer Patients in the United States

Abstract: Older adults are often exposed to multiple medications, some of which could be inappropriate or have the potential to interact with each other. Older cancer patients may be at increased risk for medication-related problems due to exposure to cancer-directed treatment. We described patterns of potentially inappropriate medication (PIM) use and potential drug-chemotherapy interactions among adults age 66+ years diagnosed with stage I-III breast, stage II-III colon, and stage I to II lung cancer. Within the Surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 35 publications
0
37
0
1
Order By: Relevance
“…The time frame for identification of PIM in patients with cancer may be problematic: many are prescribed supportive care medications considered potentially inappropriate in older adults, although these are usually administered transiently and may be specifically appropriate to treat symptoms related to cancer or cancer treatment. One study has noted a transient elevation in PIM prevalence after a lung or colon cancer diagnosis, which was mostly due to the use of supportive care medications . Most current PIM assessment tools consist of explicit criteria which account for little patient context; assessment of the appropriateness of medications could be improved with tools using implicit criteria, such as the MAI, but such tools require time and expertise for application.…”
Section: Discussionmentioning
confidence: 99%
“…The time frame for identification of PIM in patients with cancer may be problematic: many are prescribed supportive care medications considered potentially inappropriate in older adults, although these are usually administered transiently and may be specifically appropriate to treat symptoms related to cancer or cancer treatment. One study has noted a transient elevation in PIM prevalence after a lung or colon cancer diagnosis, which was mostly due to the use of supportive care medications . Most current PIM assessment tools consist of explicit criteria which account for little patient context; assessment of the appropriateness of medications could be improved with tools using implicit criteria, such as the MAI, but such tools require time and expertise for application.…”
Section: Discussionmentioning
confidence: 99%
“…MEPS respondents do not report prescription indication, a limitation common in pharmacoepidemiology research . We could not determine the appropriateness of each medication, but studies regarding older cancer survivors have suggested that potentially inappropriate use is common and increases in the year after diagnosis . We did not capture over‐the‐counter medication or supplement use, potentially underestimating the prevalence of polypharmacy in cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…40 We could not determine the appropriateness of each medication, but studies regarding older cancer survivors have suggested that potentially inappropriate use is common 12,41,42 and increases in the year after diagnosis. 43 We did not capture over-the-counter medication or supplement use, potentially underestimating the prevalence of polypharmacy in cancer survivors. These limitations highlight the need for clinically annotated data, including indication and disease severity, to understand the impact of polypharmacy on cancer outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…19 For patients who could not remember, or otherwise did not provide a response for age at diagnosis, we used a statistical multiple imputation procedure to assign time since cancer diagnosis. 27 Multiple imputation is an iterative process which uses the distribution of the observed data to estimate the true value of the missing variable. Values produced were used in regression analysis with the results pooled through statistical software to make valid inferences about the parameters and standard errors.…”
Section: Dependent Variablementioning
confidence: 99%
“…The categories were curated from published literature based on their relevance to patients with cancer, PP, or both. 22,23 The outcomes selected were based on current literature and have been either (1) well documented in cancer patients, 15,22,23,24,25,26,27,28,29,30,31 and/or (2) were considered more likely in people with PP. 32,33,34,35,36 The goal of choosing these outcomes was to provide a selective list of short-term events which could have been precipitated by the combination of drugs in a population with a lowered immune system, mostly elderly (≥ 65), and who may have been increasing their medications due to anticancer treatment.…”
Section: Dependent Variablementioning
confidence: 99%